2022
DOI: 10.1002/smll.202107882
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Hydrogen Sensors

Abstract: Hydrogen is regarded as the ultimate fuel and energy carrier with a high theoretical energy density and universality of sourcing. However, hydrogen is easy to leak and has a wide flammability range in air. For safely handling hydrogen, robust sensors are in high demand. Plasmonic hydrogen sensors (PHS) are attracting growing interest due to the advantages of high sensitivity, fast response speed, miniaturization, and high‐degree of integration, etc. In this review, the mechanism and recent development (mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 123 publications
(185 reference statements)
0
14
0
Order By: Relevance
“…More recently, the potential of plasmonic for sensitivity enhancement of hydrogen sensors has been exploited [126][127][128]. Metal and metal-alloy play key roles in the plasmonic nature of the optical field [129].…”
Section: Plasmonic Fiber Hydrogen Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, the potential of plasmonic for sensitivity enhancement of hydrogen sensors has been exploited [126][127][128]. Metal and metal-alloy play key roles in the plasmonic nature of the optical field [129].…”
Section: Plasmonic Fiber Hydrogen Sensormentioning
confidence: 99%
“…Since 2018, the Pd/Au alloy composition has attracted huge attention due to its ability to eliminate the hysteresis effect, enhance the sensitivity, and improve the response time [127,141,155,156]. Cao et al reported a D-shaped fiber coated with PdAu alloy nanostructures as shown in Figure 15 [77].…”
Section: Plasmonic Fiber Hydrogen Sensormentioning
confidence: 99%
“…When exposed to hydrogen gas, the surface of Pd metal adsorbs hydrogen molecules and decomposes them into hydrogen atoms. 42,43 Subsequently, these hydrogen atoms enter the interior of the Pd lattice, causing its expansion and forming PdH, thus changing the optical properties of Pd. 44,45 The optical properties of Pd to PdH can be calculated using the data on the refractive index (n) and extinction coefficient (k) of PdH after hydrogenation in ref.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Ai et al reviewed hydrogen sensors based on plasmonic mechanism. (26) Wang et al reviewed fiber optical hydrogen sensors. (27) Chen et al reviewed optical hydrogen sensors derived from metal hydrides.…”
Section: Introductionmentioning
confidence: 99%